2021
DOI: 10.1039/d0cb00157k
|View full text |Cite
|
Sign up to set email alerts
|

A peptidic inhibitor for PD-1 palmitoylation targets its expression and functions

Abstract: We show for the first time that PD-1 is palmitoylated, identify DHHC9 as the predominant enzyme for its palmitoylation, and reveal the molecular mechanisms underlying its effects on PD-1 stability and functions. Importantly, we also designed PD1-PALM, a competitive inhibitor of PD-1 palmitoylation, and this first-in-class molecule may inspire the development of new checkpoint inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…PD-1 ligands PD-L1 and PD-L2 are expressed on antigen-presenting cells and tumour cells. In silico motif-based prediction identified PD-1 S -palmitoylation at Cys192 between its transmembrane and cytosolic domain, which was confirmed by metabolic labelling studies [ 56 ]. PD-1 S -palmitoylation is catalysed by DHHC9.…”
Section: S -Palmitoylation Of Proteins In Adaptive Immunitymentioning
confidence: 83%
“…PD-1 ligands PD-L1 and PD-L2 are expressed on antigen-presenting cells and tumour cells. In silico motif-based prediction identified PD-1 S -palmitoylation at Cys192 between its transmembrane and cytosolic domain, which was confirmed by metabolic labelling studies [ 56 ]. PD-1 S -palmitoylation is catalysed by DHHC9.…”
Section: S -Palmitoylation Of Proteins In Adaptive Immunitymentioning
confidence: 83%
“…Yao et al . also found that PD-1 on the surface of tumor cells could be modified by zDHHC9-mediated palmitoylation, and inhibition of PD-1 palmitoylation significantly reduced the expression of PD-1 on the surface of tumor cells and inhibited tumor growth 39 . Therefore, inhibiting the palmitoylation of PD-1 on the surface of tumor cells and immune cells at the same time or combining with PD-1/PD-L1 inhibitors may be an effective treatment strategy.…”
Section: Protein Palmitoylation Regulates Pd-1/pd-l1 Signalingmentioning
confidence: 83%
“…We envision that a crystal structure of a PATi-bound DHHC would both aid in deciphering the mechanism of the cyanomethyl-mediated increase in potency and highlight opportunities for structure-based design. In addition, the capability of zDHHC20 to acylate NRas peptide, as well as recent reports of DHHC-targeted peptide inhibitors, hint at the potential of peptide scaffolds as DHHC inhibitors [48][49] . Our future work will focus on modifying small molecule and peptide scaffolds to achieve improvements in selectivity and potency.…”
Section: Discussionmentioning
confidence: 99%